Inhalant abuse: Newer trends in addiction: A case series - Rajiv Saini; Harpreet Singh; Amit Chail; Krishnendu Datta; Arka Adhvaryu (Journal of Marine Medical Society, 2022)
Inhalant abuse is common in adolescents and young people. However, awareness about its harmful effects is low, and the potential to cause dependence remains a cause of concern. Inhalant abuse is often associated with underlying novelty-seeking traits, which can also predict propensity for other substances of abuse. Inhalants are cheap, freely available, and legal to possess and escape detection in vulnerable groups. There is a need to spread awareness about the harmful effects of inhalants and devise effective primary and relapse prevention strategies.